The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10802-018-0500-0
|View full text |Cite
|
Sign up to set email alerts
|

Onset, Comorbidity, and Predictors of Nicotine, Alcohol, and Marijuana Use Disorders Among North American Indigenous Adolescents

Abstract: North American Indigenous (i.e., American Indian and Canadian First Nations) youth experience inequities in rates of substance abuse and dependence. Despite this, few longitudinal studies examine the developmental course of substance use disorders (SUD) among community-based samples of Indigenous youth. The purpose of the study was to examine onset and predictors of nicotine dependence, alcohol use disorders, marijuana use disorders, any SUD, and multiple SUDs across the entire span of adolescence among a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Our findings highlight the pervasive nature of discrimination in Aotearoa New Zealand and demonstrate that discrimination may play a role in the higher levels of hazardous drinking observed among Indigenous populations , extending work conducted with African Americans in the United States . Although our findings support the indirect pathway between discrimination and alcohol use (i.e.…”
Section: Discussionsupporting
confidence: 60%
“…Our findings highlight the pervasive nature of discrimination in Aotearoa New Zealand and demonstrate that discrimination may play a role in the higher levels of hazardous drinking observed among Indigenous populations , extending work conducted with African Americans in the United States . Although our findings support the indirect pathway between discrimination and alcohol use (i.e.…”
Section: Discussionsupporting
confidence: 60%
“…Many studies have identified a cluster of risk behaviours for adolescent smoking, including alcohol and illicit drug use [11,14–17]. These associations have been found among Indigenous adolescents of North America [22,32] and in qualitative work in Australia [23,24] with researchers noting the importance of social settings that promote sharing and experimentation with illicit substances. Our results suggest other substance use is an important risk factor for smoking for all young people.…”
Section: Discussionmentioning
confidence: 99%
“…The strong association between smoking, drinking and cannabis use clearly suggests common determinants as explained by PBT. Adolescent smoking can also serve as an indicator of risk, with those who experiment or establish smoking in early high school more likely to adopt other problem behaviours, including substance use, later in high school and adolescence [32,34]. The call for coordinated health promotion programs to address multiple risk behaviours through common determinants has been made for both Indigenous adolescents [21,32,35] and adolescents in general [15,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations